The effects on self-efficacy, motivation and perceived barriers of an intervention targeting physical activity and sedentary behaviours in office workers: a cluster randomized control trial - Victoria Blom; Emma Drake; Lena V. Kallings; Maria M. Ekblom; Carla F. J. Nooijen (BMC, 2021)
Abstract Background The importance of physical activity on health is clear, but changing behaviour is difficult. Successful interventions aiming to improve physical activity and reduce sedentary behaviour is therefore of importance. The aim of this study was to evaluate effects on motivation, self-efficacy and barriers to change behaviour from two different behavioural intervention focusing either on reducing sedentary behaviour or on increasing physical activity as compared to a waiting list control group. Methods The study was designed as a cluster randomized control trial (RCT) within two private companies. Self-efficacy, motivation and perceived barriers were together with demographic variables assessed before and after a 6-month intervention. Participant cluster teams were randomly allocated to either the physical activity intervention (iPA), the sedentary behaviour intervention (iSED), or control group. The intervention was multi componential and included motivational counselling based on Cognitive behaviour therapy and Motivational interviewing, group activities and management involvement. Group differences were determined using Bayesian multilevel modelling (parameter estimate; credible interval (CI)), analysing complete cases and those who adhered to the protocol by adhering to at least 3 out of 5 intervention sessions. Results After the intervention, the complete cases analysis showed that the iPA group had significantly higher autonomous motivation (0.33, CI: 0.05-0.61) and controlled motivation (0.27, CI: 0.04-0.51) for physical activity compared with the control group. The iSED group scored less autonomous and controlled motivation compared to the iPA group (0.38, CI: − 0.69- -0.087 respectively − 0.32, CI: − 0.57-0.07) but no significant differences compared with the control group. Among individuals that adhered to the protocol, the results showed higher scores on Exercise (3.03, CI: 0.28-6.02) and Sedentary self-efficacy (3.59, CI: 0.35-7.15) for individuals in the iPA group and on Sedentary self-efficacy (4.77, CI: 0.59-9.44) for the iSED group compared to the control group. Conclusion These findings indicate that the interventions were successful in increasing self-efficacy in each intervention group and autonomous motivation for exercise in the iPA group, in particular when actively participating in the motivational counselling sessions.